Phenotypic Detection of Metallo-β-Lactamase in Imipenem-Resistant Pseudomonas aeruginosa - Yalda Khosravi; Mun Fai Loke; Eng Guan Chua; Sun Tee Tay; Jamuna Vadivelu (The Scientific World Journal)
Carbapenems are the primary choice of treatment for severe Pseudomonas aeruginosa infection. However, the emergence of carbapenem resistance due to the production of metallo-β-lactamases (MBLs) is of global concern. In this study, 90 imipenem- (IPM- or IP-) resistant P. aeruginosa (IRPA) isolates, including 32 previously tested positive and genotyped for MBL genes by PCR, were subjected to double-disk synergy test (DDST), combined disk test (CDT), and imipenem/imipenem-inhibitor (IP/IPI) E-test to evaluate their MBLs detection capability. All three methods were shown to have a sensitivity of 100%. However, DDST was the most specific of the three (96.6%), followed by IP/IPI E-test interpreted based on the single criteria of IP/IPI ≥8 as positive (62.1%), and CDT was the least specific (43.1%). Based on the data from this evaluation, we propose that only IRPA with IP MIC >16 μg/mL and IP/IPI ≥8 by IP/IPI E-test should be taken as positive for MBL activity. With the new dual interpretation criteria, the MBL IP/IPI E-test was shown to achieve 100% sensitivity as well as specificity for the IRPA in this study. Therefore, the IP/IPI E-test is a viable alternative phenotypic assay to detect MBL production in IRPA in our population in circumstances where PCR detection is not a feasible option.